TRANSFORMASI PENDIDIKAN ISLAM: PERAN MADRASAH, PESANTREN, DAN UNIVERSITAS DALAM MENJAWAB TANTANGAN ZAMAN - ZIDAN KHALIK AL JABER; HILALLUDIN HILALLUDIN; SITI MASLAHATUL KHAER (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2026)
Islamic education in Indonesia, through madrasahs, pesantrens, and universities, plays a vital role in shaping the character and com Islamic education in Indonesia, through madrasahs, pesantrens, and universities, plays a vital role in shaping the character and competencies of the nation's generation. Each institution has a unique contribution: madrasahs focus on strengthening religious education, pesantrens emphasize the formation of morals and spirituality, while universities play a role in the development of science and technology. However, significant challenges are faced in integrating a curriculum that is relevant to the needs of the times, utilizing technology in learning, and improving the quality of educators. Synergy between these three institutions is essential to create an adaptive and innovative Islamic education system, capable of addressing global challenges and producing a generation that is intelligent, ethically upright, and prepared to face the dynamics of the times. petencies of the nation's generation. Each institution has a unique contribution: madrasahs focus on strengthening religious education, pesantrens emphasize the formation of morals and spirituality, while universities play a role in the development of science and technology. However, significant challenges are faced in integrating a curriculum that is relevant to the needs of the times, utilizing technology in learning, and improving the quality of educators. Synergy between these three institutions is essential to create an adaptive and innovative Islamic education system, capable of addressing global challenges and producing a generation that is intelligent, ethically upright, and prepared to face the dynamics of the times.